2013
DOI: 10.1002/micr.22124
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study of breast sensation after breast reconstruction: Evaluating the effects of radiation therapy and perforator flap neurotization on sensory recovery

Abstract: Without irradiation, skin overlying implants is associated with better sensation recovery than DIEP flap skin. However, with irradiation, DIEP flap skin had better sensation recovery than did skin over implants. Neurotization trended toward improvement in sensation in DIEP flaps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
84
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(85 citation statements)
references
References 49 publications
(152 reference statements)
1
84
0
Order By: Relevance
“…The evidence is particularly sparse for clinical evaluation of sexual function and outcomes in girls and adolescents with cancer, and surprisingly little is known about how to evaluate breast sexual function. 233 Research and practice expertise is also needed to better serve particularly marginalized groups, including women with cancer and sexual concerns who are older or widowed, those who identify with a sexual or gender minority group, women with physical and/or cognitive disability, and women receiving palliative or hospice care. Some women do wish to remain sexually active until the end of life; as a matter of compassion and human rights, institutional hospice care settings should ensure patient privacy and support symptom alleviation for comfortable and safe sexual activity.…”
Section: Resultsmentioning
confidence: 99%
“…The evidence is particularly sparse for clinical evaluation of sexual function and outcomes in girls and adolescents with cancer, and surprisingly little is known about how to evaluate breast sexual function. 233 Research and practice expertise is also needed to better serve particularly marginalized groups, including women with cancer and sexual concerns who are older or widowed, those who identify with a sexual or gender minority group, women with physical and/or cognitive disability, and women receiving palliative or hospice care. Some women do wish to remain sexually active until the end of life; as a matter of compassion and human rights, institutional hospice care settings should ensure patient privacy and support symptom alleviation for comfortable and safe sexual activity.…”
Section: Resultsmentioning
confidence: 99%
“…The finding of improved breast sensation postoperatively with innervation has also been demonstrated in TRAM flaps, including one randomized controlled trial . While studies compared results with and without nerve grafts, only one utilized a nerve conduit . However, there is significant variability among the studies in regards to surgical protocols, nerves and grafts utilized and postoperative sensory testing, making comparison between studies difficult …”
Section: Discussionmentioning
confidence: 95%
“…Future studies directly comparing large cohorts of immediate, staged, and delayed reconstructions, ideally prospectively, may help confirm potential benefits of the widespread use of tissue expanders, even in eventual autologous tissue reconstruction. Our study lacks patient reported outcomes and Quality of Life data, such as the BREAST‐Q, which may vary depending on the timing of reconstruction and whether the selected reconstructive option leads to an aesthetically pleasing and sensate breast . Additionally, our study is based on the protocols used at our institution, which may or may not be generalizable to other reconstructive programs.…”
Section: Discussionmentioning
confidence: 99%